PENDIDIKAN ISLAM ERA KHALIFAH USMAN BIN AFFAN DAN RELEVANSINYA DENGAN PENDIDIKAN ISLAM DI INDONESIA ERA MODERN - MENTARI PUTRI MAHARANI (UIN Kiai Ageng Muhammad Besari Ponorogo, 2024)
Islamic education during the time of Khulafaur Rasyidin as a whole can be said to be almost the same as Islamic education during the time of the Prophet Muhammad. both in terms of materials and educational institutions. Meanwhile, during this period there was also a development of Islamic education which was caused by the conditions and needs of the Muslim community at that time. The development of Islamic education at that time really depended on the state of government. If the state of government was stable and safe then Islamic education could develop, whereas if there were many problems that occurred then the process of educational development was hampered. Islamic education began to be implemented by Rasulullah SAW. After receiving orders from Allah, he called on Allah, as included in the Koran, Surah Al-Mudatstsir (74) verses 1-7. To call means to invite, and to invite and means to educate. Caliph Uthman bin Affan cared deeply about education and promoted quality education in Muslim society.